Temperate and boreal forest mega-fires: characteristics and challenges - Stephens, Scott L; Burrows, Neil; Buyantuyev, Alexander; Gray, Robert W; Keane, Robert E; Kubian, Rick; Liu, Shirong; Seijo, Francisco; Shu, Lifu; Tolhurst, Kevin G; van Wagtendonk, Jan W (Frontiers in ecology and the environment, 2014)
Mega-fires are often defined according to their size and intensity but are more accurately described by their socioeconomic impacts. Three factors - climate change, fire exclusion, and antecedent disturbance, collectively referred to as the "mega-fire triangle" - likely contribute to today's mega-fires. Some characteristics of mega-fires may emulate historical fire regimes and can therefore sustain healthy fire-prone ecosystems, but other attributes decrease ecosystem resiliency. A good example of a program that seeks to mitigate mega-fires is located in Western Australia, where prescribed burning reduces wildfire intensity while conserving ecosystems. Crown-fire-adapted ecosystems are likely at higher risk of frequent mega-fires as a result of climate change, as compared with other ecosystems once subject to frequent less severe fires. Fire and forest managers should recognize that mega-fires will be a part of future wildland fire regimes and should develop strategies to reduce their undesired impacts.